Shariah screening methodology of Securities Commission Malaysia: an analytical fiqh study - Mohd Nor, Ahmad Mawardi; Md. Sawari, Mohd. Fuad (IIUM Press, International Islamic University Malaysia, 2017)
Shariah Screening Methodology is a benchmark adopted by Securities Commission Malaysia in order to identify which listed companies are Shariah compliant. Historically, Shariah Screening Methodology of SC has gone several revisions, of which the latest methodology was revised in November 2013. The study intends to find what was being revised and the reasons behind this revision. In addition, it reviews the differences between the SC benchmark and other international benchmarks formulated by AAOIFI, Dow Jones and FTSE benchmark. This research discusses the opinions of Muslim scholars on the issue of companies with mixed income and the need for purification of the said income. Furthermore, this study identifies the Shariah rules and principles used by Securities Commission to develop and revise the benchmark. The study concludes that the Securities Commission’s Shariah Screening Methodology is the least stringent among other international benchmarks studied, but it still is an acceptable benchmark.